A força dos contatos: um estudo das redes interpessoais de profissionais da região metropolitana de Belo Horizonte - Humberto Elias Garcia Lopes (2001)
This dissertation researched professionals selected among the students of the graduate program in strategic management of the Federal University of Minas Gerais (UFMG). The focus was the impact of social embeddedness in the structural variables of the inter-personalnetworks of individuals who experienced social mobility. Using the structural approach developed by Burt (1982), this dissertation proposed a research model based on the work of Granovetter (1994), Lin, Ensel and Vaughn (1981) and Wegener (1991). The main goal of that model was to verify the existence of a direct correlation between embeddedness and the structural variables of inter-personal networks. The variablesused in this dissertation were the relationship frequency, the network structure, and the individual social status. The data were collected through a self-applicable questionnaire previously validated in itsform and content. The data were used to access some demographic information about the sample as well as to evaluate each of the considered indicators. This leads to the analysis of the missing data process, the detection of univariate and multivariate outliers, and the shape of the distribution of each indicator according to its degree of skewness and kurtosis. Since the research was quantitative it was necessary to verify the violations to the assumptions of the multivariate data analysis: normality (univaritate and multivariate), linearity, homocesdasticity, multicolinearity, and singularity. After that, the scales used in the questionnaire were refined to meet the convergent and discriminant validity of each construct. The model was tested through the confirmatory factor analysis (CFA) where the maximum likelihood method of estimation was used. The standardized estimates, the t test, thenormalized residuals matrix, and the goodness of fit measures from both measurement and structural models were used to verify the plausibility of the proposed model. The research allowed three conclusions. Firstly, there is a direct correlation between embeddedness and the frequency of the relationship in an inter-personal network. However, the data showed that embeddedness had a stronger connection with family relationships than with the non-family ones. Secondly, it was found a positive correlation between embeddedness and the network structure. But this association was not equal: the family and friendship relationships weremore significant than the academic ones. Thirdly, the research was unable to detect any connection between embeddedness and socialstatus. This result didnt find support in the theory addressed in this dissertation. Then, it is necessary to perform other investigations to verify if embeddedness and social status are really disconnected from each other or if its lack of correlation was merely casual. Even though this dissertation had lead to relevant conclusions it suffers from significantlimitations such as the small sample size and the lack of a perfect fit in the proposed model. However, despite these problems, it was possible to specify a new research agenda as well as to identify some managerial implications from the results obtained.